2022
DOI: 10.1186/s12888-022-03701-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of exposure and response prevention in obsessive-compulsive disorder: effects of habituation and expectancy violation on short-term outcome in cognitive behavioral therapy

Abstract: Background Exposure and response prevention is effective and recommended as the first choice for treating obsessive-compulsive disorders (OCD). Its mechanisms of action are rarely studied, but two major theories make distinct assumptions: while the emotional processing theory assumes that treatment effects are associated with habituation within and between exposure sessions, the inhibitory learning approach highlights the acquisition of additional associations, implying alternative mechanisms l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…Fifth, the recruitment process was stopped prematurely due to the onset of the COVID-19 pandemic and the statistical power, particularly for the detection of between-group effects, was therefore compromised. Sixth, the study misses a longterm assessment of effects of both interventions; in line with findings of Brown et al (2017) and Elsner et al (2022), a superiority of an IL-based exposure intervention might only be seen in relation to long-term outcomes (e.g., return of fear).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Fifth, the recruitment process was stopped prematurely due to the onset of the COVID-19 pandemic and the statistical power, particularly for the detection of between-group effects, was therefore compromised. Sixth, the study misses a longterm assessment of effects of both interventions; in line with findings of Brown et al (2017) and Elsner et al (2022), a superiority of an IL-based exposure intervention might only be seen in relation to long-term outcomes (e.g., return of fear).…”
Section: Discussionmentioning
confidence: 87%
“…It could be important to develop fears that a priori are assessed as probable and still threatening. Furthermore, previous results suggested that positive effects of an IL-based exposure/extinction training, which aims at mismatching expectancies, are rather seen over a long-term perspective (i.e., after further therapy sessions, after one week in an extinction retention testing) (Brown et al, 2017; Elsner et al, 2022). Thus, we cannot exclude that effects of the IL-based intervention in the present study only would have become evident at a later point of time (e.g., in tests on return of fear or in a later assessment).…”
Section: Discussionmentioning
confidence: 99%
“…Though cognitive approaches to reducing IU may be useful, behavioral changes may be equally effective; belief change is a mechanism of effective exposure interventions, which target behavioral change (Knowles & Tolin, 2022). For instance, distress-related expectancy violation during exposure predicted OCD remission in a recent study (Elsner et al, 2022); similar violation in expectancies in one's ability to tolerate uncertainty may also mediate OCD symptom reduction during exposure. Understanding how established OCD risk factors (i.e., obsessive beliefs) fit into the nomological network of IU will be an important next step in understanding the broader construct of IU and the extent to which its association with OCD symptoms is distinct or a function of other related constructs, as well as inform OCD treatment.…”
Section: Intolerance Of Uncertainty In Ocdmentioning
confidence: 99%
“…Only a handful of studies to date have explored whether prediction error during exposure relates to treatment outcomes. This hypothesis has been tested in exposure-based treatment for obsessive compulsive disorder (41)(42)(43), panic disorder (44), and post-traumatic stress disorder (45). Results have been mixed with some studies finding an association between prediction error during exposure and treatment outcomes (41,43), while other studies have found no such effects (42,45).…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis has been tested in exposure-based treatment for obsessive compulsive disorder (41)(42)(43), panic disorder (44), and post-traumatic stress disorder (45). Results have been mixed with some studies finding an association between prediction error during exposure and treatment outcomes (41,43), while other studies have found no such effects (42,45). These mixed results may be due to three limitations in the research-broadly described as conceptual, statistical, and methodological issues that are summarized below.…”
Section: Introductionmentioning
confidence: 99%